2020
DOI: 10.1016/j.seares.2020.101848
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in ichthyoplanktonic assemblages of the eastern English Channel

Abstract: ish assemblages vary through time in both abundance and diversity, often due to changes in climate. The potential consequences of these changes on the larval phase need to be considered. In the Eastern English Channel, fish larvae of 30 taxa, from surveys conducted during spring in the nineties and in 2017 with bongo nets, were used to investigate seasonal and interannual changes in larval assemblages with different statistical tests and multivariate analyses (Outlying Mean Index, Principal Coordinate Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…abundances encountered in 1995 compared to 2017 are in line with the results of DiPane et al (2020a) where this difference was observed for several species of the area. The month ofMay (1995 and appeared to be the month when the highest abundance of sole larvae was encountered.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…abundances encountered in 1995 compared to 2017 are in line with the results of DiPane et al (2020a) where this difference was observed for several species of the area. The month ofMay (1995 and appeared to be the month when the highest abundance of sole larvae was encountered.…”
supporting
confidence: 90%
“…The filtered volume of seawater was calculated using a digital flowmeter fixed at the entry of each net. The content of the first net was dedicated to calculate fish larval abundances and was fixed in a buffered-formalin seawater solution (Di Pane et al, 2020a). Fish larvae from the second net were fixed in Bouin-Hollande solution for two days and then stored in ethanol 70° for two months before histological analyses.…”
Section: Surveysmentioning
confidence: 99%
“…Past [19] and present results confirm that Clupeidae are an abundant and accessible prey for large whiting in winter. During this period, Downs herring [74] and S. sprattus [75] gather in very large numbers in the EEC-SNS to mate and spawn. The large abundance of Clupeidae in large whiting stomachs reflects that the winter spawning migration of these species in the EEC represents an important trophic opportunity for whiting during a nutrient-poor period.…”
Section: Plos Onementioning
confidence: 99%